Banks, Capital Markets, and the Monetary Transmission Mechanism. - Dimsdale, N (1994)
This paper reviews the recent literature on bank behavior and the transmission process of monetary policy. It examines the implications of asymmetric information for the credit market and the capital market and discusses the macroeconomic significance of these results. In models with imperfect information net worth is found to play a key role in generating macroeconomic fluctuations and in the monetary transmission process. The special characteristics of banks are discussed and also the conditions required for the presence of a distinct credit channel for monetary policy. Empirical evidence on the importance of the new theories is briefly reviewed including an evaluation of the role of capital market imperfections in investment and consumption and the differential impact of monetary policy on small and large firms. The lessons to be drawn from these theoretical and empirical results for the conduct of monetary policy are briefly outlined.